A mixed methods investigation of reasons underlying fear of positive evaluation. (28th December 2022) - Wilson, Gillian A.; Malivoire, Bailee L.; Cassin, Stephanie E.; Antony, Martin M.
Abstract: Fear of negative evaluation (FNE) is a hallmark feature of social anxiety disorder (SAD). There is also evidence that people with SAD fear receiving positive evaluation and that fear of positive evaluation (FPE) is distinct from FNE. However, researchers have speculated that concerns related to negative evaluation may actually underlie FPE. This study sought to advance our understanding of FPE by employing both quantitative and qualitative methods to assess the reasons underlying participants' endorsement of FPE on the Fear of Positive Evaluation Scale and the extent to which these reasons reflect FNE versus FPE in a sample of individuals with SAD ( n = 47) and a nonclinical comparison group ( n = 49). Results indicated that responses to the FPES items primarily reflected an underlying FNE. Consistent with contemporary cognitive–behavioural theories of SAD, fear of proximal or eventual negative judgement emerged as the most common reason for participants' responses on the FPES. However, participants reported other reasons that did not reflect FNE, such as fear of hurting people's feelings and uncertainty associated with positive evaluation. All of the reasons underlying participants' ratings on the FPES were reported by both the SAD group and the nonclinical comparison group; however, individuals with SAD endorsed each of the reasons to a greater extent. These findings suggest that the FPES does not exclusively assess FPE as intended; however, the emergence and endorsement of reasons other than FNE suggest that FPE exists as a distinct construct.